The Difficulties of Reading Cultural-based Texts among Yemeni EFL Learners - Almuslimi, Fazee (International Journal of Language and Literary Studies, 2020)
The present study aimed at discovering the difficulties that level two students in the English Department, Faculty of Education, Sana'a University-Sana'a in reading comprehension when reading cultural-based texts. To achieve the study objectives, a test was administered in which participants were required to read two texts; one was cultural-based and the other was ordinary. The study method was descriptive. 51 participants were randomly selected from the whole population (180 students). The obtained data from the instrument was analyzed by calculating frequencies and paired sample t-test using SPSS program. The results revealed that even though students face difficulties when reading cultural texts, there is no significant statistical difference in their performance in the cultural based test and the ordinary one in the three subskills under investigation in this study (the main idea, guessing meaning from the text, and making inferences). Some recommendations were suggested. It was ended with some important recommendations related to its results in which teachers and learners should take into account enhancing and activating both of cultural and structural schemata.